Pea protein isolate-alginates bio-composite Film: Enhancing performance with pomegranate flower extract - Mohammad Pilehforooshha; Mohsen Zandi; Ali Ganjloo; Nazila Dardmeh (Polymer Testing)
The present study aimed to develop a novel composite film based on pea protein isolate (PPI)-alginate containing pomegranate flower extract (PFE). The effects of various PPI to alginate ratios (1:1, 1:3, and 1:5) and PFE concentrations (0 %, 5 %, and 10 % v/v) on the on the bio-composite films. FTIR and DSC analyses revealed molecular interactions and enhanced thermal stability with increased protein content and decreased PFE concentration. XRD results indicated higher crystallinity in films with higher protein content and lower extract concentration. FESEM images displayed smooth and compact structures in films with high protein content without extract, resulting in increased tensile strength, elastic modulus, and contact angle. Functional properties, including water vapor and oxygen permeability, water solubility, moisture content, and swelling ratio, decreased by 56.58 %, 46.71 %, 60.21 %, 54.54 %, and 58.67 %, respectively, in films with a 1:5 protein to alginate ratio containing 0 % PFE compared to films with a 1:1 ratio containing 10 % PFE. Increased protein content and extract concentration enhanced opacity and antioxidant activity but reduced biodegradability rate, although all films degraded by over 75 % within 60 days. Films containing 10 % extract exhibited the highest antimicrobial activity and total phenolic content. Release studies demonstrated controlled rapid and slow release of the extract in aqueous and fatty simulants, respectively. The developed active bio-composite film shows significant potential for applications in medicine, cosmetics, pharmaceuticals, and food industries.